2020
DOI: 10.3389/fcell.2020.560766
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Reveals Multi Pigmentation Genes Affecting Dorsoventral Pattern in Avian Body

Abstract: Certain animals exhibit a special dorsoventral pattern with a lighter ventral side compared to the dorsal one and this phenomenon was preserved in the long-term evolution process. Birds also retain this trait. Recently, Inaba et al. (2019) found that ASIP (agouti signal protein) regulated interconversion between different melanocyte types leads to dorsal stripe pattern, which may partly explain the birds' dorsoventral plumage color difference. In this study, we used the embryo samples of LBM (light brown mottl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…Based on a literature search, we identified 5 genes located in the inverted region that could be potential candidate for pigmentation: TYR, RAB-38, OCA2, DCT and GPR143, 11,[73][74][75][76][77][78] and one related to migratory behavior or restlessness: NPAS2. [79][80][81] To assess if the gene function could be different in quails with and without the inversion, we annotated the SNP dataset with SnpEff v.4.3t 51 using the GTF annotation file from the Japanese quail genome.…”
Section: Genomic Data Snp Calling and Filteringmentioning
confidence: 99%
“…Based on a literature search, we identified 5 genes located in the inverted region that could be potential candidate for pigmentation: TYR, RAB-38, OCA2, DCT and GPR143, 11,[73][74][75][76][77][78] and one related to migratory behavior or restlessness: NPAS2. [79][80][81] To assess if the gene function could be different in quails with and without the inversion, we annotated the SNP dataset with SnpEff v.4.3t 51 using the GTF annotation file from the Japanese quail genome.…”
Section: Genomic Data Snp Calling and Filteringmentioning
confidence: 99%
“…To investigate the relationship between the phenotype and EDNRB2 mRNA expression level, we examined the RNA-seq results of our previous study about the pigment deposition process during the embryonic period [ 14 ]. The results showed that the expression level of EDNRB2 increased with increasing melanic areas on the body surface of duck embryos (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The numbers in the diamond represent R 2 values. d The FPKM (fragments per kilobase of transcript per million mapped reads) values of the EDNRB2 gene in duck embryos with different melanin deposition areas were calculated based on our previous RNA-seq data [ 14 ]. The expression of EDNRB2 showed a significant increasing trend with increasing melanin area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome data of liver and sebum from mallard and pekin at 2, 4, and 6 weeks of age was downloaded from National Genomics Data Center (China National Center for Bioinformation) from the project number PRJCA002795, PRJCA002803, PRJCA002808, and PRJCA002807 [48]. Transcriptome data of the skin tissue was downloaded from project number PRJCA003516 [79]. Raw reads were filtered using Trimmomatic (v 0.39) [80] and subjected to align the duck pan-genome using STAR (v2.7.1a) [81].…”
Section: Functional Assay Of Igf2bp1 and Mitfmentioning
confidence: 99%